Análise da cinética de decomposição térmica da casca de urucum (bixa orellana l.) - Breciani, João Guilherme Fraga (2024)
This study aims to investigate the drying kinetics and thermal decomposition of annatto husks (Bixa orellana L.) in a nitrogen atmosphere. The analysis was performed through physical-chemical, thermal, and thermodynamic characterizations of the residue. Based the data obtained from the physico-chemical characterization, the residue's energy potential was verified, showing a low ash content and high calorific value. The thermal characterization was carried out using thermogravimetric analysis of the residues at different heating rates, which allowed for the determination of the material's peak, ignition, and burnout temperatures during the pyrolysis process. From this data, a drying kinetics study was performed, where the Page model provided the best fit to the experimental data. Additionally, the thermal decomposition kinetics of the material was studied using global and multicomponent models. Among the global models, Friedman, FWO, KAS, and Vyazovkin models were analyzed, but none were suitable for experimental representation. For the multicomponent models, consecutive reactions and independent parallel reactions were analyzed, both showing excellent fits, with TG deviations below 2.6% for all heating rates analyzed. Finally, in the thermodynamic characterization, the values of enthalpy, Gibbs free energy, and entropy indicate that the thermal decomposition of annatto husks in a nitrogen atmosphere is an endothermic and non-spontaneous process.